Structural change out of agriculture: labor push versus labor pull - Francisco Alvarez-Cuadrado; Markus Poschke (Institute for the Study of Labor (IZA), 2009)
The process of economic development is characterized by substantial rural-urban migrations and a decreasing share of agriculture in output and employment. The literature highlights two main engines behind this process of structural change: (i) improvements in agricultural technology combined with the effect of Engel's law of demand push resources out of the agricultural sector (the labor push hypothesis), and (ii) improvements in industrial technology attract labor into this sector (the labor pull hypothesis). We present a simple model that features both channels and use it to explore their relative importance. We evaluate the U.S. time series since 1800 and a sample of 13 industrialized countries starting in the 19th century. Our results suggest that, on average, the labor pull channel dominates. This contrasts with popular modeling choices in the recent literature.
urn:nbn:de:101:1-2009070395
Keywords: O11; O41; 330; Growth; structural change; Strukturwandel; Drei-Sektoren-Hypothese; Landflucht; Grüne Revolution; Industrielle Beschäftigung; Arbeitsnachfrage; USA; Industriestaaten